Value Innovation in Medical Tourism - Paul, Geo; Nair, Raghu Pradeep (Prabandhan: Indian Journal of Management, 2015)
The global medical tourism sector is growing exponentially and is emerging as a major growth area in healthcare services. India has carved out a unique place for itself in providing low-cost and advanced global healthcare services. Medical tourism can be the next Indian success story after Information Technology if it succeeds in making the competition from other Asian countries irrelevant. However, the medical tourism industry in India cannot hope to gain sustainable competitive advantage if the healthcare providers and government agencies do not work in coordination and cooperation in this direction. The article accentuates that if India wants to position itself as a destination of choice in medical tourism, it will have to look beyond developing countries in Asia and Africa. India will have to create fresh market share in developed nations like America and Europe through targeted marketing activities focusing on FTA (foreign tourist arrivals) at its airports from these countries. Furthermore, practicing managers in the medical tourism sector must realize the important role played by the Internet in the growth of medical tourism and leverage information technology. The Indian state also has to play a critical role in fostering inter-state cooperation in developing medical tourism and make over unfriendly regulatory procedures into ’hospitality services’ for international patients.